Level of Civil Servant Legal Awareness in Providing Public Services - Sudirman, Muh.; ., Mustaring (KnE Social Sciences, 2024)
This research aims to find out; (1) the level of legal awareness of Parepare municipal civil servants; (2) the level of quality of public service for Civil Servants of Parepare municipality; and (3) the significance of the influence of the level of legal awareness on the quality of public services for civil servants in Parepare City. This research is a survey. The population consists of two groups, namely, (1) all civil government officials working at the Parepare City secretariat who are registered in 2022, which has 134 people. A total sample of 35 people was taken using stratified random sampling, and a total sample of 35 people was taken using accidental sampling. Data were collected through questionnaires, observation, documentation, and interviews, and were analyzed using descriptive statistics and simple regression. The research results show that; (1) the level of legal awareness of civil servants at the regional secretariat office of Parepare City in providing public services seen from the aspects of legal knowledge, understanding of the law, legal attitudes, and patterns of legal behavior, is included in the low category; (2) the level of quality of public services in the field of civil servant administration at the regional secretariat office of Parepare City is seen from the aspects of friendliness, simplicity, clarity and certainty, openness (transparency), efficiency, economy, equitable justice, and timeliness of service, including in medium category; (3) there is a significant influence of the quality level of legal awareness on the quality of public services in the field of administration of civil servants at the regional secretariat office of Parepare City. Keywords: legal awareness, civil servant, public service